2001
DOI: 10.1208/ps030429
|View full text |Cite
|
Sign up to set email alerts
|

Allometric scaling of xenobiotic clearance: Uncertainty versus universality

Abstract: Statistical analysis and Monte Carlo simulation were used to characterize uncertainty in the allometric exponent (b) of xenobiotic clearance (CL). CL values for 115 xenobiotics were from published studies in which at least 3 species were used for the purpose of interspecies comparison of pharmacokinetics. The b value for each xenobiotic was calculated along with its confidence interval (CI). For 24 xenobiotics (21%), there was no correlation between log CL and log body weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
64
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 82 publications
(33 reference statements)
4
64
0
1
Order By: Relevance
“…High r 2 values (ca. greater than 0.90) have been cited for most of the allometric relationships reported in the literature (Mahmood and Balian, 1996;Hu and Hayton, 2001). By definition, r 2 is the fraction of the total squared error explained by the model.…”
mentioning
confidence: 99%
“…High r 2 values (ca. greater than 0.90) have been cited for most of the allometric relationships reported in the literature (Mahmood and Balian, 1996;Hu and Hayton, 2001). By definition, r 2 is the fraction of the total squared error explained by the model.…”
mentioning
confidence: 99%
“…Notwithstanding the limitations of interspecies scaling and the power law relationship debate, allometric scaling data indicate that fixed exponents of 2/3 or 3/4 may not be universally applicable in pharmacokinetics (24,28,29,31,33,38,44,47). Our analyses showed that the 95% CI encompassed both 2/3 and 3/4 for CL of artemether and artemisinin, whereas the upper limit of the 95% CIs for mefloquine, quinine, and chloroquine (0.63, based on reanalysis of a previous study [33]) were all Ͻ0.65 (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…where Y is the pharmacokinetic parameter (e.g., CL or V z ), W is the body weight of the species, a is the coefficient, and b is the allometric exponent (19,24,38).…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some physiologic, species-specific model parameters (e.g., volume flow rates) can be translated across species using the allometric equation, an empirical power law that relates the biological parameter to body weight (25,26). Hence, the mathematical model can be parameterized using animal data and then ''scaled-up'' to human and used to predict the biodistribution of the same drug in the clinic (27).…”
Section: From Mouse To Manmentioning
confidence: 99%